The value of using patient‐reported outcomes for health screening during long‐term follow‐up after paediatric stem cell transplantation for nonmalignant diseases - Joëll E. Bense; Nicole Guilonard; Femke Zwaginga; Anne M. Stiggelbout; Marloes Louwerens; Hilda Mekelenkamp; Arjan C. Lankester; Arwen H. Pieterse; Anne P. J. dePagter (Health Expectations)
Abstract Introduction The assessment of using patient‐reported outcomes (PROs) within comprehensive care follow‐up programmes, specifically focused on health screening, remains largely unexplored. PROs were implemented in our late effects and comprehensive care programme after paediatric hematopoietic stem cell transplantation (HSCT) for nonmalignant diseases. The programme focuses solely on screening of physical and mental health and on discussing PROs during the consultation. Methods The primary method of this study was semistructured interviews to explore the perspective of both patients and healthcare providers' (HCP) on the use of PROs, which were thematically analyzed. Additionally, an explorative quantitative approach with patient‐reported experience measures (PREMS) was used, with a pretest–posttest design, to assess whether the use of PROs was accompanied by more patient‐centred care. Results From the patient‐interviews (N = 15) four themes were extracted: use of PROs (1) help to discuss topics; (2) make the patients feel understood; (3) create a moment of self‐reflection; and (4) make consultations more efficient. Pre‐ and postimplementation analysis of PREMs (N = 40) did not show significant differences in terms of patient‐centeredness. Conclusion Our results demonstrate the added value of integrating PROs for health screening purposes within the long‐term follow‐up programme after paediatric HSCT, as perceived by both patient and HCP. With the active use of PROs, patients are stimulated to consciously assess their health status. Patient Contribution This study included patients as participants. Caregivers were approached if patients were below a certain age. Additionally, preliminary results were shared with all patients (including nonparticipants) during a patient conference day.